2020
DOI: 10.1002/cplu.202000563
|View full text |Cite
|
Sign up to set email alerts
|

A Series of Discrete Dichloride Dihydrates: Characterisation and Symmetry Effects

Abstract: A series of three discrete dichloride dihydrates [Cl2(H2O)2]2− have been isolated with different triaminocyclopropenium (TAC) cations and with different crystallographic symmetries. The cluster exhibits D2h symmetry with the tris(dimethylamino)cyclopropenium cation [C3(NMe2)3]+, C2h symmetry with the fluorinated cation [C3(N(CH2CF3)2)(NBu2)2]+ (containing two 2,2,2‐trifluoroethyl substituents) and C2v symmetry with the more fluorinated [C3(N(CH2CF3)2)2(NBu2)]+ cation. The effect of symmetry on the infrared spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“… Mid‐IR spectra in the O−H stretching region for encapsulated chloride hydrates in the solid state: (a) [Cl(H 2 O)] − ; (b) [Cl 2 (H 2 O)] 2− ; (c) D 2h [Cl 2 (H 2 O) 2 ] 2− ; (d) C 2h [Cl 2 (H 2 O) 2 ] 2− ; (e) C 2v [Cl 2 (H 2 O) 2 ] 2− ; (f) [Cl 2 (H 2 O) 4 ] 2− ; (g) [Cl 2 (H 2 O) 6 ] 2− ; (h) [Cl 4 (H 2 O) 4 ] 4− ; (i) {[Cl(H 2 O)] − } ∞ [6,9,11–14] …”
Section: Monohalide Hydratesmentioning
confidence: 99%
“… Mid‐IR spectra in the O−H stretching region for encapsulated chloride hydrates in the solid state: (a) [Cl(H 2 O)] − ; (b) [Cl 2 (H 2 O)] 2− ; (c) D 2h [Cl 2 (H 2 O) 2 ] 2− ; (d) C 2h [Cl 2 (H 2 O) 2 ] 2− ; (e) C 2v [Cl 2 (H 2 O) 2 ] 2− ; (f) [Cl 2 (H 2 O) 4 ] 2− ; (g) [Cl 2 (H 2 O) 6 ] 2− ; (h) [Cl 4 (H 2 O) 4 ] 4− ; (i) {[Cl(H 2 O)] − } ∞ [6,9,11–14] …”
Section: Monohalide Hydratesmentioning
confidence: 99%
“…We have recently been investigating the synthesis and properties of partially‐fluorinated TAC salts. We have previously reported that treatment of tetrachlorocyclopropene with NH(CH 2 CF 3 ) 2 and NBu 3 leads primarily to a mixture of [C 3 (N(CH 2 CF 3 ) 2 ) 2 (NBu 2 )]Cl and [C 3 (N(CH 2 CF 3 ) 2 )(NBu 2 )Cl]Cl, and that the latter can be further treated with the secondary amine NHBu 2 to give [C 3 (N(CH 2 CF 3 ) 2 )(NBu 2 ) 2 ]Cl [9] . By using the less bulky tertiary amine NEt 3 instead of NBu 3 , a small amount of the diaminochloro‐TAC cation [C 3 (N(CH 2 CF 3 ) 2 )(NEt 2 )Cl] + is produced (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“… The structures of known discrete chloride hydrates (a) [Cl(H 2 O)] − ; (b) [Cl 2 (H 2 O) 2 ] 2− ; (c) [Cl 2 (H 2 O)] 2− ; (d) [Cl 2 (H 2 O) 4 ] 2− ; (e) [Cl 2 (H 2 O) 6 ] 2− [1,9,17–19] …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations